Restriction enzyme analysis of Listeria monocytogenes strains associated with food-borne epidemics. - Wesley, I V (1991)
Listeria monocytogenes (serotype 4b) has caused four major food-borne epidemics in North America. In this study, L. monocytogenes isolates from the Nova Scotia (Canada), Boston (Mass.), and Los Angeles (Calif.) outbreaks were examined by restriction enzyme analysis with the endonuclease HhaI. Human isolates (n = 32) from the 1981 Canadian outbreak were compared with a strain recovered from coleslaw, which was epidemiologically incriminated as the vehicle of infection. After HhaI digestion, 29 of 32 isolates exhibited the restriction enzyme pattern of the reference coleslaw isolate. The restriction enzyme patterns of the nine clinical isolates from the 1983 Massachusetts outbreak were identical to each other but differed from those of raw milk isolates recovered from sources supplying the pasteurizer. Isolates (n = 48) from the 1985 California outbreak were evaluated. The restriction enzyme patterns of the L. monocytogenes isolates from humans and from the suspect cheese samples were identical to those of four of five cheese factory environmental isolates. Isolates from each of these outbreaks exhibited a restriction enzyme pattern that was characteristic of that outbreak. The case with which restriction enzyme analysis can be applied to all serotypes of L. monocytogenes argues for its use in the epidemiology of L. monocytogenes.